1999
DOI: 10.1046/j.1360-0443.1999.9479612.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of fatal opioid overdose

Abstract: There has been increasing recognition of the problem of fatal opioid overdose. This review examines the pharmacological basis of respiratory depression following opioid administration. Respiration is controlled principally through medullary respiratory centres with peripheral input from chemoreceptors and other sources. Opioids produce inhibition at the chemoreceptors via mu opioid receptors and in the medulla via mu and delta receptors. While there are a number of neurotransmitters mediating the control of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
430
1
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 532 publications
(447 citation statements)
references
References 52 publications
(61 reference statements)
8
430
1
8
Order By: Relevance
“…Previous research has shown that there are many factors that contribute to heroin overdose, such as differing metabolic rates, recent changes in patterns of use affecting tolerance, use in combination with other drugs or alcohol, and the purity of the heroin used. 3,4 However, investigation of these factors in the absence of information about the user's state of mind immediately prior to the overdose in question assumes that the event was accidental.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that there are many factors that contribute to heroin overdose, such as differing metabolic rates, recent changes in patterns of use affecting tolerance, use in combination with other drugs or alcohol, and the purity of the heroin used. 3,4 However, investigation of these factors in the absence of information about the user's state of mind immediately prior to the overdose in question assumes that the event was accidental.…”
Section: Introductionmentioning
confidence: 99%
“…2 Epidemiologic studies have identified several factors that increase the risk of overdose, including (1) concomitant use of other drugs, such as benzodiazepines and alcohol; (2) low tolerance level; and (3) impaired physical health status of the user. 3 Warner-Smith et al 4 documented that drug users who have experienced a nonfatal overdose suffer from peripheral neuropathy, lung infections, cardiac complications, and cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…This increased frequency of overdose in heroin injectors is most likely due to the physiological effects heroin has and the nature of a heroin overdose; there is often a fine line between acute respiratory suppression and when heroin dosage becomes toxic causing respiratory failure, hypoxia and potentially death (Jolley, Bell, Rafferty, Moxham, & Strang, 2015;White & Irvine, 1999).…”
Section: Proportion Reporting Overdosementioning
confidence: 99%